Persepsi orang tua peserta didik kelas IV SD terhadap platform pembelajaran dalam jaringan (daring) IPA selama masa sindemi - Hernanto, Muhdi Dendy; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study was to determine the perceptions of the parents of grade IVSD Angkasa Lanud Adi Soemarmo on the use of platforms in science learning. Respondents in this study were 16 parents of grade IV SD Angkasa Lanud Adi Soemarmo. This research is a descriptive qualitative research. Data collection was carried out by interviewing teachers and parents of students. The validity technique used is source triangulation. Data analysis using data reduction, data presentation, and levers. The final results of this study found that parents' perceptions of the science learning platform used were not yet effective, because the platformused was only Whatsapp. The use of the Whatsapp Platform is also only for providing video material and for teaching assignments. The use of other platforms has also been implemented but has not been maximal in delivering material due to the bad internet..